2020
DOI: 10.5530/pj.2020.12.144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Chemical Compound of Essential Oil from Ketumbar (Coriandrum sativum L.) Leaves with Gc-Ms

Abstract: Ketumbar (Coriandrum sativum L.) is a plant that is widely used as a spice, especially in cooking spices. This plant has a distinctive aroma. The distinctive aroma that is owned because this plant contains essential oils. 1 Phytochemical screening results of coriander seeds have diverse secondary metabolites, including steroids, flavonoids, saponins, tannins, coumarin, 2 volatile compounds 3 and coriander leaves are contain phenolic acid, poliyphenols, glycosides, saponins, flavonoids and tannins. 4,5 These co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…As a result of our earlier investigation and literature searching, we were able to identify a total of nine major chemicals in CSL (Table 1) (Gurning et al 2020;Satyal and Setzer 2020). The GeneCards database was searched for targets linked to COVID-19, and the results revealed that there were 4,585 targets connected to COVID-19 and a total of 195 possible targets of 9 active compounds of CSL.…”
Section: Investigation Of Potential Targetsmentioning
confidence: 98%
See 1 more Smart Citation
“…As a result of our earlier investigation and literature searching, we were able to identify a total of nine major chemicals in CSL (Table 1) (Gurning et al 2020;Satyal and Setzer 2020). The GeneCards database was searched for targets linked to COVID-19, and the results revealed that there were 4,585 targets connected to COVID-19 and a total of 195 possible targets of 9 active compounds of CSL.…”
Section: Investigation Of Potential Targetsmentioning
confidence: 98%
“…According to International Organization of Standards (1998) and Guring et al (2020), CSL contain several essential oil such as linalool, limonene, α-pinene, geraniol, and α-terpineol. All of these active compounds from CSL have shown abundant health benefits (Gurning et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Coriander (Coriandrum sativum) [64][65][66] Reduction in arterial blood pressure of anesthetized animals have been noted at dose 1-30 mg/ml crude extract -Ca 2+ channel blocking and cholinergic property.…”
Section: Cinnamon (Cinnamomum Zeylanicum)mentioning
confidence: 99%